PEMANFAATAN MEDIA TIK SIMULASI SEBAGAI SUPLEMEN EKSPERIMEN DALAM PEMBELAJARAN ALAT UKUR - Imas Setiana Esti Galih; Agus Suyatna; Viyanti Viyanti (Jurnal Pembelajaran Fisika, 2014)
The objectives of this research were to find out the increasing of learning result in the cognitive domain, to grow skill of science process, to develop activities, to form characters and to grow students’ learning attitudes by using ICT simulation media as an experimental supplement in learning the measuring devices. This research was conducted in Junior High School 1 Way Kenanga, Tulang Bawang Barat. The research population was all students of Grade VII meanwhile the sample was class VII A. The sampling technique was taken using cluster random sampling. Based on the results of the research by using ICT simulation media as an experimental supplement in learning the measuring devices showed that there were improvements in cognitive domain learning results, growth of students’ science process skills, development of students’ learning activities, form of students’ learning characters and growth students’ learning attitudes.Tujuan dari penelitian ini yaitu untuk mengetahui peningkatan hasil belajar ranah kognitif, menumbuhkan keterampilan proses sains, mengembangkan aktivitas, membentuk karakter dan menumbuhkan sikap belajar siswa dari pemanfaatan media TIK simulasi sebagai suplemen eksperimen dalam pembelajaran alat ukur. Penelitian ini dilaksanakan di SMPN 1 Way Kenanga, Tulang Bawang Barat. Populasi penelitian yaitu seluruh siswa kelas VII sedangkan sampel yaitu kelas VII A. Teknik pengambilan sampel menggunakan Cluster Random Sampling. Berdasarkan hasil penelitian dengan memanfaatkan media TIK simulasi sebagai suplemen eksperimen dalam pembelajaran alat ukur menunjukkan bahwa terjadi peningkatan hasil belajar ranah kognitif, tumbuhnya keterampilan proeses sains siswa, berkembangnya aktivitas belajar siswa, terbentuknya karakter belajar siswa dan tumbuhnya sikap belajar siswa.Kata kunci: aktivitas, karakter, keterampilan proses sains, media TIK simulasi, suplemen eksperimen